Thromboelastography to Monitor Clotting/Bleeding Complications in Patients Treated with the Molecular Adsorbent Recirculating System - Esther B. Bachli; Jörg Bösiger; Markus Béchir; John F. Stover; Reto Stocker; Marco Maggiorini; Eberhard L. Renner; Beat Müllhaupt; Reto A. Schuepbach (Critical Care Research and Practice)
Background. The Molecular Adsorbent Recirculating System (MARS) has been shown to clear albumin-bound toxins from patients with liver failure but might cause bleeding complications potentially obscuring survival benefits. We hypothesized that monitoring clotting parameters and bed-side thromboelastography allows to reduce bleeding complications. Methods. Retrospective analysis of 25 MARS sessions during which clotting parameters were monitored by a standardized protocol. Results. During MARS therapy median INR increased significantly from 1.7 to 1.9 platelet count and fibrinogen content decreased significantly from 57 fL−1 to 42 fL−1 and 2.1 g/L to 1.5 g/L. Nine relevant complications occurred: the MARS system clotted 6 times 3 times we observed hemorrhages. Absent thrombocytopenia and elevated plasma fibrinogen predicted clotting of the MARS system (ROC 0.94 and 0.82). Fibrinolysis, detected by thromboelastography, uniquely predicted bleeding events. Conclusion. Bed-side thromboelastography and close monitoring of coagulation parameters can predict and, therefore, help prevent bleeding complications during MARS therapy.